Melatonin and N-acetylcysteine have beneficial effects during hepatic ischemia and reperfusion - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
This study was designed to study the effects of Melatonin (Mel) and N-Acetylcystein (NAC) on hepatic ischemia/ reperfusion (I/R) injury in rats. For this purpose Wistar albino rats were subjected to 45 minutes of hepatic ischemia followed by 60 minutes of reperfusion period. Melatonin (10 mg/kg) or NAC (150 mg/kg) were administered alone or in combination, intraperitoneally, 15 minutes prior to ischemia and just before reperfusion. Serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels were determined to assess liver functions. Liver tissues were taken for determination of malondialdehyde (MDA) levels, an end product of lipid peroxidation; glutathione (GSH) levels, a key antioxidant; protein carbonyl concentration (protein oxidation) (PO), a specific marker of oxidative damage of proteins; and myeloperoxidase (MPO) activity, as an indirect index of neutrophil infiltration. Plasma ALT and AST activities were higher in ischemia/reperfusion group than in control. They were decreased in the groups given Mel, NAC or the combination. Hepatic GSH levels, significantly depressed by I/R, were elevated to control levels in the combination group, whereas treatment with Mel or NAC alone provided only a limited protection. Hepatic MDA and PO levels, and MPO activity were significantly increased by I/R. The increase in these parameters were partially decreased by Mel or NAC alone, whereas treatment with the combination reduced these values back to control levels. In conclusion, considering the dosages used, Mel appeared to be significantly more potent than NAC in reversing the oxidative damage induced by I/R. Our findings show that Mel and NAC have beneficial effects against the I/R injury and due to their synergistic effects, when administered in combination, may have a more pronounced protective effects on the liver. (C) 2003 Elsevier Science Inc. All rights reserved.
Keywords: ischemia/reperfusion; liver; lipid peroxidation; glutathione; myeloperoxidase; protein oxidation; LIPID-PEROXIDATION; MYELOPEROXIDASE ACTIVITY; REACTIVE OXYGEN; TISSUE-INJURY; FREE-RADICALS; LIVER-INJURY; RAT MODEL; ANTIOXIDANT; GLUTATHIONE; MECHANISMS